Fishermen's Perception of the Benefits of Using ICT in Relationship with Fishermen's Income and Stakeholder Role Strategies : A Case Study in Pati, Central Java - Ika Suciati; Indah Susilowati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2022)
The potential of fisheries resources is still massive as well as the challenges.Â One of the challenges faced in the fisheries sector is climate change occurring massively. Climate change that occurs disrupts the productivity and activities of fishermen. Fishermen live with uncertainty because their livelihoods are directly related to nature. So that fishermen are required to be able to adapt and mitigate to climate change that is occurring rapidly. Information innovation and communication are widely developed to help fishermen in sea activities. The technology created is available in various forms, such as android-based applications, SMS broadcasts, Whatsapp groups, GPS, Fishfinder, etc. The objective of this study is to identify fishermen's perception of the benefits of technology and service communication used, ICT relationship with fishermen's income, and stakeholder role strategies in the use of ICT. The mix-method approach is used to acknowledge study objectives using the software SPSS 23 and Atlas. Ti 8. The result shows that fishermen's perception of the benefits of ICT namely facilitating communication, reducing production costs, improving safety, increasing fishermen's knowledge, and increasing income. There is a relationship between the use of ICT and fishermen's income, as well as stakeholders who have an important role in the use of ICT in the fishing community.